2014
DOI: 10.1016/j.vaccine.2014.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus gastroenteritis among children less than 5 years of age in private outpatient setting in urban India

Abstract: Burden of rotavirus gastroenteritis (RVGE) in outpatient setting in India is not fully understood. A prospective study was undertaken to describe RVGE among Indian children less than 5 years of age presenting in outpatient departments with acute gastroenteritis (AGE). This study was conducted at 11 outpatient departments (OPDs) of private pediatric clinics in urban areas of India. A total of 605 eligible children were enrolled at OPDs. Stool samples of the subjects were collected and tested for presence of rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…It is reported that rotavirus infections are at peak in the season of winter [12,21]. But in our study the rotavirus infections were evenly distributed among all the seasons of the year.…”
Section: Discussioncontrasting
confidence: 68%
“…It is reported that rotavirus infections are at peak in the season of winter [12,21]. But in our study the rotavirus infections were evenly distributed among all the seasons of the year.…”
Section: Discussioncontrasting
confidence: 68%
“…The positive rate was higher than that of developed countries, such as England (14.3%) (Sethi et al, 2001); lower than that of some developing countries, such as Thailand (30%) (Chieochansin et al, 2016) and India (23%) (Namjoshi et al, 2014); and similar to the positive rate of rotavirus detection in Sudan (16%) (Magzoub et al, 2013). The danger to males was higher, and the ratio of infected males to females was 1.6:1.…”
Section: Discussionmentioning
confidence: 60%
“…Enteric viruses, especially rotavirus, have been considered as the leading pathogens of pediatric diarrhea worldwide [19, 20]. Other major enteric viruses causing childhood diarrhea included norovirus, human adenovirus(HAdV), human astrovirus, and sapovirus [17, 2123].…”
Section: Discussionmentioning
confidence: 99%